Occurrence of Tomato Leaf Miner Tuta Absoluta Meyrick(Lepidoptera:Gelechiidae) in Duhok Region (A) - Assaf, Lazgeen H.; Hassan, Feyroz R.; Rasheed, Halgurd I.; Sadiq, Mohammad A.; Ismael, Rezgar M.; Ahmed, Mohammad Sh.; Saeed, Salah A.; Salih, Farhad M. T. (Science Journal of University of Zakho, 2015)
The aim of this work is to investigate the population density and infestation percentage of Tuta absoluta on tomato crop Lycopersicum esculentumMill under field conditions in three locations at Duhok province/ Kurdistan region/ northern of Iraq in 2012. The average number of mines/ leaflet, larvae/ leaf and larvae/ fruit during the study season were 2.33, 0.34 and 0.61 respectively. The results showed a significant differences in infestation percentage and number of male per trap among the three locations. The highest percentage of infestation was recorded in September as 74.00, 72.00 and 60.00 for Summel, Shekhan and Zawita respectively. The maximum number of males/ trap/ week was 1205.40 recorded on 26/8/2012 in Summel. Concerning the use of pheromone trap for pest monitoring, linear regression analysis results was significant between trap catches and the number of mines per leaf and the infestation rate of leaves